Investigation of Changes in the Surface Structure of LixNi0.8Co0.15Al0.05O2 Cathode Materials Induced by the Initial Charge - Hwang, Sooyeon; Chang, Wonyoung; Kim, Seung Min; Su, Dong; Kim, Dong Hyun; Lee, Jeong Yong; Chung, Kyung Yoon; Stach, Eric A. (AMER CHEMICAL SOC, 2014)
We use transmission electron microscopy (TEM) to investigate the evolution of the surface structure of LixNi0.8Co0.15Al0.05O2 cathode materials (NCA) as a function of the extent of first charge at room temperature using a combination of high-resolution electron microscopy (HREM) imaging, selected area electron diffraction (SAED), and. electron energy loss spectroscopy (EELS). It was found that the surface changes from the layered structure (space group R (3) over barm) to the disordered spinel structure (Fd (3) over barm), and eventually to the rock-salt structure (Fm (3) over barm), and that these changes are more substantial as the extent of charge increases. EELS indicates that these crystal structure changes are also accompanied by significant changes in the electronic structure, which are consistent with delithiation leading to both a reduction of the Ni and an increase in the effective electron density of oxygen. This leads to a charge imbalance, which results in the formation of oxygen vacancies and the development of surface porosity. The degree of local surface structure change differs among particles, likely due to kinetic factors that are manifested with changes in particle size. These results demonstrate that TEM, when coupled with EELS, can provide detailed information about the crystallographic and electronic structure changes that occur at the surface of these materials during delithiation. This information is of critical importance for obtaining a complete understanding of the mechanisms by which both degradation and thermal runaway initiate in these electrode materials.
Keywords: LITHIUM-ION BATTERIES; THERMAL-STABILITY; PHASE-TRANSITION; LI; INSTABILITY; MICROSCOPY; EELS